Integrated photonic devices for realizing photonic quantum computing: part 3 - Leo, Chang Jing (Nanyang Technological University, 2023)
This project seeks to examine the use of Fourier plane imaging in the evaluation of lidar systems. We show how a Fourier plane imaging set-up is constructed. The sample was simultaneously illuminated using a combination of a source of collimated white-light, a diffracting element, and a microscope objective lens. By varying the bandpass filter, several images were collected. We evaluate the results collected and examine the application of Fourier plane imaging in the evaluation of lidar systems.